PELATIHAN PERSONAL BRANDING DAN STRATEGI KOMUNIKASI BAGI TUTOR MUDA (TROOPERS) ARMIDALE ENGLISH COLLEGE (AEC) - Sutarjo, Moch. Armien Syifaa; Diniati, Anisa; Mukhlisiana, Lusy (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2023)
In the midst of competition in the digital era like today, every individual is required to be able to always improve their abilities in order to continue to compete. Every individual must improve their abilities. Two things that are very important in facing a competitive business environment are personal branding and communication strategies. Therefore, we, the Telkom University Community Service team, would like to fully support the Armidale English College (AEC) Troopers to develop their knowledge and skills regarding personal branding and communication strategies by providing offline training. Building a good personal branding requires continuous knowledge enrichment and training. With the knowledge of the importance of building a strong personal branding and managing good communication strategies, it is hoped that these young tutors can set a good example for their juniors and also prepare themselves to face the increasingly fierce competition in the future where each individual must be able to showcase their own strengths. By participating in the training and mentoring program for a predetermined period of time. Partners will gain specific knowledge and skills in implementing personal branding, from introduction to evaluation.